The Athletic Victory as a Value in the Pindaric Odes - Goggaki, Κ. (Nikephoros (Institut für Alte Geschichte und Altertumskunde, Karl-Franzens-Universität Graz), 2004)
Pindar, one of the most fundamental representatives of Greek choral lyric poetry, which flourished in the Archaic period, is the exclusive poet of competitive (athletic) victory. This is due to the fact that his works, the Epinikian Odes, or paeans, have survived in their entirety and, chiefly, to the fact that the victories in the sacred contests, or games, served as cause for his poetic creations. Thus, despite the fact that he was a professional poet, Pindar nevertheless formulated the athletic ideal in accordance with his belief that the games comprise the continuity of the heroic past. This paper investigates Pindar’s ideas, which influence the way he views the competitive, or athletic, victory as a value. The term ‘value’ is used here in the sense of intellectual, spiritual, religious and political value, but also in the sense of personal honor and the honor of the family heritage. Consequently, although Pindar is emphatically the poet of joy, he nevertheless makes his moments even brighter with indirect comparisons of the distant past and future prospects, putting his entire character into his poetry. The poet - whose work, according to J.B. Bury, reflects the authentic quality of the Greek intellect– comes and goes between the world of religion and that of myth, using graphic descriptions in such a manner that they create a vivid mental picture, thus giving new character to a theme. Pindar, in completing his Ode to Victory (Niki) and idealizing the victors, cultivates and expresses the athletic ideal. At the same time, by uniting all the Greeks around the sacred games by virtue of his paeans, he renders himself somewhat of a national poet. His poetic word, based, as mentioned earlier, on a bright vision of reality but also on a low-key poetic tongue, formulates into a vision-depicting poetry which deserves, according to C.M. Bowra, to be considered as the earthly correlation to Apollo’s music and the song of the Muses on Mt. Olympus which Pindar himself considers the archetype of music at those supreme moments when all differences are resolved and all guilt is expiated by the power of the life-giving word.